Pembuatan Alat Peraga Sistem Kerja Lampu Rem Belakang Sepeda Motor sebagai Media Pembelajaran Jurusan Teknik Sepeda Motor Kelas XI di SMK Negeri 1 Nisam - Fatimah Zuhra; Abubakar Abubakar; Islami Fatwa (Jurnal Sains dan Teknologi, 2024)
The learning process can proceed well if aided by the presence of teaching aids.Because the teaching aid for the electrical system of the motorcycle rear brake light was not available, this teaching aid was created.The purpose of this research is to determine: (1) the method of creating a teaching aid for the rear motorcycle brake light system, (2) the feasibility level of the teaching aid for the rear motorcycle brake light system, and (3) the students' response to the teaching aid for the rear motorcycle brake light system.This research uses a development research approach, also known as Research and Development (R&D). The Research and Development (R&D) method is a research method used to produce a specific product and test its effectiveness. This research will be conducted at SMK Negeri 1 Nisam. The implementation will be carried out in the even semester of the 2024/2025 academic year. This research and development uses 3 methods in data collection. The methods used are observation, questionnaires, and documentation. The data analysis technique used in this research is descriptive analysis, which presents the results of product development in the form of learning media, testing the validity and suitability of the product for implementation in the electrical system of motorcycle rear brake lights.The results of the research on the development of teaching media props, which have gone through several stages such as potential issues, data collection, product design, product validation, design revision, product testing, until it became a teaching media prop for the electrical system of the motorcycle brake light. The results obtained from the material expert validation were 91.31% by validator 1 and 95.13% by validator 2. The media expert validation results were 97.91% by validator 1 and 97.91% by validator 2. The results of the students' responses to the teaching aids, after calculations, showed a total response score of 506 out of 572 overall. With a final score percentage of 88.46% and the qualification of the developed teaching aids' response being in the "Very Good" category.